Assessment of the concentration of nitric oxide in exhaled air (FeNO) in primary school children in Krakow and Ruzomberk in relation to air pollution in these cities. - M. Czubaj-Kowal; T. Friediger; M. Połcik-Jastrząb; M. Sokołowski; Z. Hudakova (Medičnì Perspektivi)
The measurement of the exhaled nitric oxide (FeNO) is a recognized biomarker in the detection and monitoring of airway inflammatory infections, this including asthma. Due to its simplicity, and noninvasiveness, it is more and more widely used in diagnostics of children. Few studies indicate the relationship between FeNO and atmospheric air pollution. The goal of the following study was the measuring of FeNO for 8-9 year old children in Krakow and Ruzomberok and relating the results of these measurements to the level of air pollution in the PM10 and PM2,5 range. 250 children aged 8-9 (125 in Krakow and 125 in Ruzomberok) attending third grades of primary schools, have constituted the research group. The measurement has been taken in accordance with the applicable standards with the application of a MediSOFT Belgium analyzer with a disposable head with an antibacterial filter. The results of the measurements have been referred to the PM10 and PM2,5 concentration of particulate matter in the air. Within the group of 125 children participating in the study in Krakow, the FeNO levels were normal for 104 (83.2%) children and increased for 21 (16.8%) children. During the period of the study, the average PM10 concentration was 55,7 µg/m3 and PM2,5 was 37.0 µg/m3. As far as the group of 125 children examined in Ruzomberok, the FeNO levels were correct (5-20 ppb) for 114 (91,2%) children and increased (21-55) for 11 children (8.8%). During the period of the study, the average PM10 concentration was 24.1 µg/m3 and PM2,5 was 15.4 µg/m3. As one can see from the comparison, 1.9 times more increased FeNO levels have been recorded in Krakow than in Ruzomberok (18.6 vs 8.8%), and, within the range of the heavily increased values (>50 ppb), this difference was as much as 4 times greater (3.2% vs 0.8%). These results correlate with the PM10 and PM2,5 levels in Krakow, which are respectively 2.3 and 2.4 times higher than those in Ruzomberok.